Production of CCL20 from lung cancer cells induces the cell migration and proliferation through PI3K pathway. Issue 5 (10th March 2016) - Wang, Beibei; Shi, Lin; Sun, Xiaoru; Wang, Lingyan; Wang, Xiangdong; Chen, Chengshui
Abstract: Tumour inflammatory microenvironment is considered to play a role in the sensitivity of tumour cells to therapies and prognosis of patients with lung cancer. The expression of CCL20, one of the critical chemoattractants responsible for inflammation cells recruitment, has been shown overexpressed in variety of tumours. This study aimed at investigating potential mechanisms of CCL20 function and production in human non‐small cell lung cancer (NSCLC). Expression of CCL20 gene and protein in lung tissues of patients with NSCLC and NSCLC cells (A549) were determined. The interleukin (IL)‐1β‐induced signal pathways in A549 and the effect of CCL20‐induced A549 cell migration and proliferation were determined using migration assays and cell‐alive monitoring system. Mechanisms of signal pathways involved in the migration of CCL20 were also studied. We initially found that NSCLC tumour tissues markedly overexpressed CCL20 in comparison with normal lung samples. In addition, IL‐1β could directly promote CCL20 production in lung cancer cells, which was inhibited by extracellular signal‐regulated kinase (ERK)1/2 inhibitor, p38 mitogen‐activated protein kinase (p38 MARP) inhibitor or PI3K inhibitors. CCL20 promoted lung cancer cells migration and proliferation in an autocrine manner via activation of ERK1/2‐MAPK and PI3K pathways. Our data indicated that IL‐1β could stimulate CCL20 production from lung cancer cells through the activation of MAPKs and PI3K signal pathways, and the auto‐secretion of CCL20 could promote lung cancer cell migration and proliferation through the activation of ERK and PI3K signal pathways. Our results may provide a novel evidence that CCL20 could be a new therapeutic target for lung cancer.